Protein Phosphatase-1 Activates CDK9 by Dephosphorylating Ser175 - Ammosova, Tatiana (Public Library of Science, 2011)
The cyclin-dependent kinase CDK9/cyclin T1 induces HIV-1 transcription by phosphorylating the carboxyterminal domain (CTD) of RNA polymerase II (RNAPII). CDK9 activity is regulated by protein phosphatase-1 (PP1) which was previously shown to dephosphorylate CDK9 Thr186. Here, we analyzed the effect of PP1 on RNAPII phosphorylation and CDK9 activity. The selective inhibition of PP1 by okadaic acid and by NIPP1 inhibited phosphorylation of RNAPII CTD in vitro and in vivo. Expression of the central domain of NIPP1 in cultured cells inhibited the enzymatic activity of CDK9 suggesting its activation by PP1. Comparison of dephosphorylation of CDK9 phosphorylated by ((32)P) in vivo and dephosphorylation of CDK9's Thr186 analyzed by Thr186 phospho-specific antibodies, indicated that a residue other than Thr186 might be dephosphorylated by PP1. Analysis of dephosphorylation of phosphorylated peptides derived from CDK9's T-loop suggested that PP1 dephosphorylates CDK9 Ser175. In cultured cells, CDK9 was found to be phosphorylated on Ser175 as determined by combination of Hunter 2D peptide mapping and LC-MS analysis. CDK9 S175A mutant was active and S175D – inactive, and dephosphorylation of CDK9's Ser175 upregulated HIV-1 transcription in PP1-dependent manner. Collectively, our results point to CDK9 Ser175 as novel PP1-regulatory site which dephosphorylation upregulates CDK9 activity and contribute to the activation of HIV-1 transcription.